Prevalence of sarcopenia and its association with dysphagia in cancer patients who require rehabilitation - Hidetaka Wakabayashi; Rimiko Takahashi; Naoko Watanabe; Hideyuki Oritsu; Yoshitaka Shimizu (Journal of Rehabilitation Medicine, 2017)

(untitled)
Objective: To assess the prevalence of sarcopaenia and the association between sarcopaenia, activities of daily living, and dysphagia in cancer patients who require rehabilitation. Methods: A cross-sectional study was performed in 83 consecutive cancer patients referred to the Department of Rehabilitation Medicine. Skeletal muscle index was calculated as total psoas muscle area assessed via abdominal computed tomography divided by height squared. Sarcopaenia was diagnosed using the Asian Working Group for Sarcopenia criteria. Activities of daily living were evaluated with the Barthel Index. Dysphagia was assessed with the 10-item Eating Assessment Tool (EAT-10). Results: Study participants were 50 males and 33 females (mean age 71, standard deviation 12 years). Sarcopaenia was observed in 66 (80%) patients. The median Barthel Index score was 55 (interquartile range: 25–75). Thirty-five (42%) patients were diagnosed as having dysphagia. Logistic regression analysis of dysphagia adjusted for sarcopaenia, Barthel Index score, age, and reason for hospitalization showed that sarcopaenia (odds ratio (OR) 3.616; 95% confidence interval (95% CI) 0.926–14.114; p = 0.064) and Barthel Index score (OR 0.984; 95% CI 0.966–1.002; p = 0.073) did not reach statistical significance. Conclusion: The prevalence of sarcopaenia in cancer patients who require rehabilitation is very high. The power of this study was too low to observe a significant association between sarcopaenia and dysphagia.